Chronic health impairment due to 2,3,7,8-tetrachloro-dibenzo-p-dioxin exposure - Pelclova, Daniela; Fenclova, Zdenka; Urban, Pavel; Ridzon, Petr; Preiss, Jan; Kupka, Karel; Malik, Jan; Dubska, Zora; Navratil, Tomas (Neuro endocrinology letters, 2009)
OBJECTIVES: The aim of this study, performed in 2008, was to evaluate the consequences of severe occupational intoxication with 2,3,7,8-tetrachloro-dibenzo-p-dioxin (TCDD) that occurred during production of the herbicide trichlorophenoxyacetic acid in the period 1965-1968. DESIGN: Examination of 11 men, mean age 64.4+/-1.5 years, included: internal and neurological examination, eye fundus examination, TCDD in plasma, thyroid-stimulating hormone (TSH), testosterone and serum lipids, ultrasonography of the carotid artery, nerve conduction study (NCS), electroencephalography (EEG), visual evoked potential (VEP), Lanthony test of acquired visual impairment, single photon emission computer tomography (SPECT) of the brain, neuropsychological examination and carbohydrate-deficient transferrin (CDT), a marker of chronic ethanol intake. RESULTS: Mean TCDD level in 2008 was still 274.0+/-181.2 pg/g blood lipids (reference level is 2-3 pg/g). All (100%) patients had residues of chloracne/chloracne consequences, atherosclerotic changes on the eye fundus and plaques in the carotid arteries. Progression of intima-media thickness (IMT) from a mean of 0.84+/-0.14 mm in 2003 to 1.09+/-0.18 mm in 2008 was observed. Ninety-one per cents of patients had impairment in SPECT of the brain; and 55% of patients had hyperfixation of the perfusion indicator as a measure of increased neuronal activity. Additionally, 91 % of patients were treated for hyperlipidaemia, 73 % for hypertension, 55 % for diabetes type 2, 45 % for ischemic heart disease, and 36 % for psychological disorders. The Lanthony test demonstrated acquired dyschromatopsia in 80 % of patients. Mean colour confusion index (CCI) was 1.438, which indicates impairment since 2003, when the index was 1.302. CDT was in the normal range and did not correlate with CCI. Neuropsychological status appeared stabilized in all 8 patients examined, with impairment in one or more parameter (memory, attention, verbal fluency, psychomotor speed, motorics) in comparison to the norm. CONCLUSION: Forty years after intoxication, the blood level of TCDD is still 100 times higher than in the general population. Other PCDD/Fs were not elevated. A high percentage of subjects suffer from neurological and vascular disorders. No association of alcohol consumption with neurological impairment was seen, and the highly significant correlation between CCI and TCDD blood concentration suggests that acquired colour impairment was associated with TCDD but not with alcohol consumption. IMT significantly increased during past 5 years. The patients obviously need complex treatment, including intense hypolipidaemic and antidepressant therapy.
Keywords: Environmental Pollutants; látky znečišťující životní prostředí; Prevalence; Triglycerides; Chronic Disease; chronická nemoc; Middle Aged; mužské pohlaví; prevalence; Polychlorinated Dibenzodioxins; Cholesterol; Follow-Up Studies; následné studie; Occupational Exposure; Humans; pracovní expozice; triglyceridy; lidé středního věku; polychlorované dibenzodioxiny; lidé; Male; cholesterol